Management of Refractory Noninsulinoma Pancreatogenous Hypoglycemia Syndrome with Gastric Bypass Reversal: A Case Report and Review of the Literature. (7th October 2015) - Rao, Bhavana B.; Click, Benjamin; Eid, George; Codario, Ronald A.
Abstract : Background . Roux-en-Y gastric bypass (RYGB) is a commonly performed, effective bariatric procedure; however, rarely, complications such as postprandial hypoglycemia due to noninsulinoma pancreatogenous hypoglycemia syndrome (NIPHS) may ensue. Management of refractory NIPHS is challenging. We report a case that was successfully treated with RYGB reversal. Case Report . A 58-year-old male with history of RYGB nine months earlier for morbid obesity presented for evaluation of postprandial, hypoglycemic seizures. Testing for insulin level, insulin antibodies, oral hypoglycemic agents, pituitary axis hormone levels, and cortisol stimulation was unrevealing. Computed tomography (CT) scan of the abdomen was unremarkable. A 72-hour fast was completed without hypoglycemia. Mixed meal testing demonstrated endogenous hyperinsulinemic hypoglycemia (EHH) and selective arterial calcium stimulation testing (SACST) was positive. Strict dietary modifications, maximal medical therapy, gastrostomy tube feeding, and stomal reduction failed to alleviate symptoms. Ultimately, he underwent laparoscopic reversal of RYGB. Now, 9 months after reversal, he has markedly reduced hypoglycemia burden. Discussion . Hyperfunctioning islets secondary to exaggerated incretin response and altered intestinal nutrient delivery are hypothesized to be causative in NIPHS. For refractory cases, there is increasing skepticism about the safety and efficacy of pancreatic resection. RYGB reversal may be successful.